Prevalence of heterophoria in a population of school children in central China: the Anyang Childhood Eye Study - Jie Hong; Jing Fu; Yi-Di Wang; Bo-Wen Zhao; Lei Li (International Journal of Ophthalmology, 2020)
AIM: To investigate the prevalence of heterophoria and the relationship between heterophoria and refractive error in a school-based study conducted in central China. METHODS: A total of 2363 7th-grade children were recruited into the cross-sectional school-based Anyang Childhood Eye Study (ACES) by cluster sampling method. Heterophoria was examined using alternate cover and cover-uncover testing. The Maddox rod and prism test were conducted at 33 cm and 6 m distance fixation. Uncorrected viual acuity (UCVA) and best-corrected viual acuity (BCVA) were recorded as logarithm of the minimum angle of resolution (logMAR) with cycloplegic autorefraction by administrating of Mydrin-P and 1.0% cyclopentolate. Hyperopia was defined as the spherical equivalent (SE) refraction of +0.50 D or greater, and higher hyperopia was defined as +2.00 D or greater. Emmetropia was defined as the SE refraction in the range of -0.49 to +0.49 D, and myopia was in the SE refraction range from -0.50 D to less. RESULTS: Totally 2260 students in grade 7 were examined. Response rate among eligible children was 95.64%. Totally 486 children, 22.66% of the population, were diagnosed with heterophoria in which 479 were diagnosed with exophoria at near distance, and 6 with esophoria. Totally 89 (4.15%) children were diagnosed with heterophoria in which 82 had exophoria, and 7 had esophoria at far distance. Exophoria was common at near fixation (22.33%). Myopia was examined to be related to exophoria at near distance (OR 3.03, 95%CI 2.33-3.95) and far distance fixation (OR 1.90, 95%CI 1.09-3.32). CONCLUSION: Exophoria is a predominant heterophoria for 7th-grade junior school in central China. Significant associations are discovered between heterophoria and refractive error. Hyperopia is associated with esophoria, and myopia is associated with exophoria.